2014
DOI: 10.1038/srep05985
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal processing of tactile stimuli in autistic children

Abstract: Altered multisensory integration has been reported in autism; however, little is known concerning how the autistic brain processes spatio-temporal information concerning tactile stimuli. We report a study in which a crossed-hands illusion was investigated in autistic children. Neurotypical individuals often experience a subjective reversal of temporal order judgments when their hands are stimulated while crossed, and the illusion is known to be acquired in early childhood. However, under those conditions where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 60 publications
4
40
1
1
Order By: Relevance
“…Increased noise is believed to contribute to sensory symptomology in ASC (Pellicano 2013), for instance, vision may have an atypical effect on the experience, or expectation of being touched. Our findings also fit with the recent observation that tactile judgements are less affected in participants with ASC when the arms are crossed over the body midline (Wada et al 2014). This suggests that tactile spatial representations may be less affected by a visual frame-of-reference in ASC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Increased noise is believed to contribute to sensory symptomology in ASC (Pellicano 2013), for instance, vision may have an atypical effect on the experience, or expectation of being touched. Our findings also fit with the recent observation that tactile judgements are less affected in participants with ASC when the arms are crossed over the body midline (Wada et al 2014). This suggests that tactile spatial representations may be less affected by a visual frame-of-reference in ASC.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study examining tactile temporal order judgements between the hands has indicated that children with ASC do not produce the typical performance detriment when their hands are crossed (Wada et al 2014). Although this is a purely tactile task, the hands crossed effect has been attributed to the visual frame of reference affecting tactile perception, which suggests that this multisensory effect may be atypical in ASC.…”
Section: Introductionmentioning
confidence: 99%
“…The result was partly consistent with previous studies reporting that individuals with ASD have disturbances in body representations (Cascio et al, 2012a; Paton et al, 2012; Palmer et al, 2015). Previous studies investigating motor learning (Haswell et al, 2009) and tactile temporal order judgment (Wada et al, 2014) suggested that the disturbances of body representations reported in individuals with ASD are explainable by a strong weight on proprioception. Interestingly, in the present study, we found that a subjective feeling of difficulty in social skills and communications (subscales of the AQ score) was strongly correlated with weak body ownership of the rubber hand.…”
Section: Discussionmentioning
confidence: 99%
“…This is indeed the case in autistic children. They are characterized by greater reliance on proprioceptive information39, and show a significantly smaller crossed-hand effect than neurotypical children30. Hence, the greater reliance in proprioception of children with autism generates a bias in the weighting of anatomical and external spatial information during the TOJ crossed-hand task.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to assess increases in the judgment reversals caused by the arm crossing manipulation, we computed the so-called sum of confusions ( SC ), defined as the sum of the differences between the response functions in the crossed and uncrossed conditions (respectively, P c and P u ) using the formula described in Wada and colleagues30, and reported in the Supplementary Materials. We also contrasted the differences between the response functions in the uncrossed and crossed conditions across the schizotypy groups.…”
Section: Methodsmentioning
confidence: 99%